Implementasi Peraturan Menteri Pekerjaan Umum Republik Indonesia Nomor: 03/PRT/M/2013 Pasal 35 Tentang Pemilihan Tempat Pembuangan Akhir - Asyfah, Dinda; Dalimunthe, Dermina; Kurniawan, Puji (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The problem in this research is the implementation of the Regulation of the Minister of Public Works of the Republic of Indonesia Number 03/PRT/M/2013 Article 35 concerning Selection of Final Disposal Sites in Padangsidimpuan City. The type of research used is field research with a qualitative approach. The primary data source in this research is Padangsidimpuan City Environment and Community Service employees. Meanwhile, secondary data are books and scientific journals that are considered relevant to this research. Data collection techniques use observation, interviews and documentation with qualitative descriptive data analysis techniques. The results of this research show that the implementation carried out by the Environmental Service is first, waste sorting which is carried out manually by scavengers. Second, waste processing still uses the Open Dumping system, namely just throwing away waste without any processing. Third, supervision of final disposal sites, namely creating guard posts and people responsible for controlling piles of rubbish at final disposal sites. Then the supporting factor for the Padangsidimpuan City final disposal site is that long before regulations regarding final disposal sites were formed, the final disposal site in Simatohir village already existed. The surrounding environment at the Padangsidimpuan City landfill is also still surrounded by residents' gardens, where air pollution caused by burning smoke from the landfill can be controlled, as can the lechate from the landfill. Then the inhibiting factors for moving the Padangsidimpuan City landfill from Simatohir village to Batang Bahal require large funds, air pollution, and the absence of socialization from the government.